Bioinspired Perspiration‐Wicking Electronic Skins for Comfortable and Reliable Multimodal Health Monitoring (Adv. Funct. Mater. 23/2022) - Xu, Yanting; Guo, Wei; Zhou, Shiqing; Yi, Haokun; Yang, Guoqing; Mei, Shuxing; Zhu, Kanhao; Wu, Hao; Li, Zhuo (Advanced functional materials, 2022)
Bioinspired Perspiration Wicking Inspired by the active liquid transport phenomenon in nature, in article number 2200961, Hao Wu, Zhuo Li, and co‐workers develop a biomimetic Au/TPU/CM based e‐skin with dual porosity and a surface energy gradient to unidirectionally drain sweat away from the skin, preventing signal degradation and wearing discomfort caused by perspiration accumulation.